Genome-Wide Epigenetic Characterization of Tissues from Three Germ Layers Isolated from Sheep Fetuses - Capra, Emanuele; Toschi, Paola; Del Corvo, Marcello; Lazzari, Barbara; Scapolo, Pier A.; Loi, Pasqualino; Williams, John L.; Stella, Alessandra; Ajmone-Marsan, Paolo (Frontiers in Genetics, 2017)
DNA methylation of regulatory and growth-related genes contributes to fetal programming which is important for maintaining the correct development of three germ layers of the embryo that differentiate into different tissues and organs, and which persists into adult life. In this study, a preliminary single tissue epigenetic screen was performed to define genomic regions that are involved in fetal epigenome remodeling. Embryonic ectodermic tissues (origin of nervous tissue), mesenchymal tissues (origin of connective and muscular tissues), and foregut endoderm tissues (origin of epithelial tissue), from day 28 sheep foetuses were collected the distribution of methylated CpGs was analysed using whole-genome bisulfite sequencing (WGBS). Patterns of methylation among the three tissues showed a high level of conservation of hypo-methylated CpG islands CGIs, and a consistent level of methylation in regulatory genetic elements. Analysis of tissue specific differentially methylated regions, revealed that 20% of the total CGIs differed between tissues. A proportion of the methylome was remodelled in gene bodies, 5’UTRs and 3’UTRs (7, 11, and 11 %, respectively). Genes with overlapping differentially methylated regions in gene bodies and CGIs showed a significant enrichment for tissue morphogenesis and development pathways. The data presented here provides a “reference” for the epigenetic status of genes potentially involved in the maintenance and regulation of fetal developmental during early life, a period expected to be particularly prone to epigenetic alterations induced by environmental and nutritional stressors.